2015
DOI: 10.2174/1381612820666141013120459
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in Immunopathology of Atherosclerosis: A Target for Diagnostics and Therapy

Abstract: Immunopathology plays important roles in the development of different life-threatening diseases, such as atherosclerosis and its consequences (acute myocardial infarction and stroke), cancer, chronic inflammatory diseases. Effective modulation of the immune system may significantly increase the efficacy of prevention and therapy efforts. Currently there are no marketed drugs capable of normalizing immune system function in an intrinsic and comprehensive way. Here, we describe a test system designed for complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…Immunohistochemistry analysis demonstrated that both grossly normal-appearing sites and atherosclerotic lesions of the human aorta contained TNF-α, a highly relevant marker of M1 macrophage [43]. In the intima of grossly normalappearing sites of the aorta and in atherosclerotic lesions, cells expressing TNF-α were found predominantly located in deeper portions of the intima.…”
Section: Phenotypes Of Macrophages In Atherosclerotic Plaquesmentioning
confidence: 99%
“…Immunohistochemistry analysis demonstrated that both grossly normal-appearing sites and atherosclerotic lesions of the human aorta contained TNF-α, a highly relevant marker of M1 macrophage [43]. In the intima of grossly normalappearing sites of the aorta and in atherosclerotic lesions, cells expressing TNF-α were found predominantly located in deeper portions of the intima.…”
Section: Phenotypes Of Macrophages In Atherosclerotic Plaquesmentioning
confidence: 99%
“…Atherosclerosis is the most severe and life-threatening complication of diabetes which is characterized by the inflammation of the vascular wall and formation of atherosclerotic plaques caused by the infiltration and accumulation of lipid-laden macrophages [5,6]. Despite a long history of investigation of the inflammatory nature of atherosclerosis, the early events leading to the activation of endothelial cells and circulating monocytes are still questionable, and biomarkers for the initial stages of atherosclerosis are needed [5].…”
Section: Introductionmentioning
confidence: 99%
“…AS is similar to cancer in certain aspects and has been referred to as a cancer-like disease (37,38); AS and cancer are chronic and progressive, and the inducing factors are very similar. In addition, the pathological mechanisms are similar, involving genetic and environmental elements.…”
Section: Discussionmentioning
confidence: 99%